Tikladong Tagalog - Rodriguez, Marial Grace Lopez; Guadalupe, Jocelyn T. (Quezon City College of Music, University of the Philippines Diliman, 2017.)
The project aims to make available piano scores of Laguna folksongs to students and teachers for their awaress of our rich culture and tradition; promote Tagalog as the mother tongue and stories of the people in Laguna; familiarize children with their own music as gifts passed on by their ancestors; and encourage other Filipino musicians to compose or arrange music for our own Filipino people for the enrichment of our culture.
Submitted May 2017.
Undergraduate student project (BM Music Education)--University of the Philippines Diliman.
Keywords: Music -- Instruction and study; School music -- Instruction and study -- Philippines; Folksongs -- Philippines -- Laguna Province